Photodynamic sensitizers modulate cytoskeleton structural dynamics in neuronal cells - Dubey, Tushar; Chinnathambi, Subashchandrabose (Cytoskeleton, 2021)
The neuronal cytoskeleton plays a crucial role in maintaining cell integrity and functioning of neurons. Cytoskeleton deformities have been reported to be associated with neurodegenerative diseases thus; cytoskeleton can be targeted for therapeutic strategies. The therapeutic application of photosensitive molecule is termed as photodynamic therapy (PDT). PDT has been applied in the field of dermatology, cancer biology, and antimicrobial therapy. PDT induces several changes in cells, which include induction of apoptosis, DNA damage, and induction of inflammatory response. PDT has been also reported to modulate cytoskeleton such as actin dynamics. The in vitro studies suggested that PDT using dyes such as Toluidine Blue and Rose Bengal effectively modulated the actin cytoskeleton, neurite outgrowth, tubulin, and Tau aggregation. In this review, we focused on the effect of photosensitized molecules on various cytoskeleton proteins. We hypothesize that PDT could have potency against Alzheimer's disease and other neurodegenerative disorders.
Keywords: Actin; Alzheimer' cytoskeleton modulation; neuronal cytoskeleton; photodynamic therapy; s disease; Tubulin